Management of Amavata Through Vaitarana Basti w.s.r to Rheumatoid Arthritis - Murshida Banu; Waheeda Banu (AYUSHDHARA, 2024)
Amavata is one of the crippling disease- causing serious agonizing painful conditions. Some of the symptoms of Amavata can correlated with Rheumatoid arthritis. Rheumatoid arthritis is a common form of inflammatory arthritis, occurring throughout the world and in all ethnic groups. The prevalence of RA is approximately 0.8-1.0% in Europe and South Asia, with a female to male ratio 3:1. Acharya Chakradatta mentioned treatment modalities for Amavata are Langhana, Swedana, Tikta, Deepana, Katu Dravya, purgatives, intake of Sneha and Application of enemas. Teekshna basthi such as Vaitarana basti is indicated in the treatment of Amavata since it possesses qualities like Amapachana, Srotoshodhana and Vatakaphahara. It has Vata kapha pacifying properties and helps in removing Avarana of Vata by Kapha. By using this Chikitsa Siddanta a case of Amavata was successfully treated and marked improvement was observed in signs and symptoms after treatment. Here a case report on Amavata has been discussed along with its effective management with Vaitarana Basti.